Layered MoS2 Hollow Spheres for Highly‐Efficient Photothermal Therapy of Rabbit Liver Orthotopic Transplantation Tumors. Issue 15 (1st March 2016) - Tan, Longfei; Wang, Shengping; Xu, Ke; Liu, Tianlong; Liang, Ping; Niu, Meng; Fu, Changhui; Shao, Haibo; Yu, Jie; Ma, Tengchuang; Ren, Xiangling; Li, Hong; et al.
Abstract : Combining photothermal therapy (PTT) with clinical technology to kill cancer via overcoming the low tumor targeting and poor therapy efficiency has great potential in basic and clinical researches. A brand‐new MoS2 nanostructure is designed and fabricated, i.e., layered MoS2 hollow spheres (LMHSs) with strong absorption in near‐infrared region (NIR) and high photothermal conversion efficiency via a simple and fast chemical aerosol flow method. Owing to curving layered hollow spherical structure, the as‐prepared LMHSs exhibit unique electronic properties comparing with MoS2 nanosheets. In vitro and in vivo studies demonstrate their high photothermal ablation of cell and tumor elimination rate by single NIR light irradiation. Systematic acute toxicity study indicates that these LMHSs have negligible toxic effects to normal tissues and blood. Remarkably, minimally invasive interventional techniques are introduced to improve tumor targeting of PTT agents for the first time. To explore PTT efficiency on orthotopic transplantation tumors, New Zealand white rabbits with VX2 tumor in liver are used as animal models. The effective elimination of tumors is successfully realized by PTT under the guidance of digital subtraction angiography, computed tomography, and thermal imaging, which provides a new way for tumor‐targeting delivery and cancer theranostic application. Abstract : Layered MoS2 hollow spheres (LMHSs) are fabricated by a fast and continuous chemical aerosol flow method. The prepared LMHSs preserve strong absorption in the near‐infrared (NIR) region and have high photothermal conversion efficiency. High tumor targeting and therapy efficiency are obtained by transarterial administration under the guide of digital subtraction angiography, infrared, and computed tomography imaging using rabbit liver tumor as model.